Activity-Based Therapy: From Basic Science to Clinical Application for Recovery After Spinal Cord Injury. (July 2017) - Behrman, Andrea L.; Ardolino, Elizabeth M.; Harkema, Susan J.
Abstract : Background and Purpose: Collaboration between scientists and clinicians effectively accelerated translation of scientific evidence for activity-based therapies (ABTs) into rehabilitation. This article addresses the basic scientific findings of activity-dependent plasticity that led to locomotor training, an ABT, and its principles to advance recovery in adult and pediatric populations with spinal cord injury (SCI). Expansion to new therapies based on these common principles is highlighted, for example, epidural stimulation. The article also describes a recently developed measure, the Neuromuscular Recovery Scale (NRS), and its psychometric properties. Summary of Key Points: Locomotor training has led to recovery of walking in some individuals with motor-incomplete SCI even years after injury. Recent studies resulted in individuals with motor-complete SCI regaining some voluntary movements and standing in the presence of epidural stimulation. The level of success for locomotor training and epidural stimulation appears dependent on spinal networks maintaining the appropriate central state of excitability for the desired task. As these new advances in restorative therapies required an outcome measure that measured performance without compensation, the NRS was developed. The NRS has strong psychometric properties in adults, and a pediatric version is under development. Application of locomotor training in children is still novel. Preliminary evidence suggests that locomotor training can improve trunk control and also foster participation in children with chronic SCI. Recommendations for Clinical Practice: ABTs may effectively promote neuromuscular recovery and improve function and participation in adults and children post-SCI. Evaluation of outcomes with valid measures, such as the NRS, is necessary to document the ability to perform functional tasks and to assess progress as function improves.